Development of electro-chemical sensor for determination of molybdenum (vi) contain in biological fluids - Маторіна, Катерина Вячеславівна (Eastern-European Journal of Enterprise Technologies, 2015)
Theelectro-chemicalsensorfordeterminationofmolybdenum (VI) concentrationwiththeusingofthetriplemetal – polymeric complex bromopyrogallol red – polyvinylpyrrolidone - molybdenum (VI) as electrode – active substance of film plasticized membrane had been elaborated. The electrode-analytical characteristics of constructed sensor had been fixed: dynamic range (2-5 рС); the slope of electrode function - 27 mV/pC detection limit Сmin= 8·10-8 mol/l; the optimal range of pH sensor operation is 6,0 – 8,0; conditioning time – 48 h; response time – 1-2 minutes; lifetime – 12 months. The effect of the inorganic electrolytes presence in internal and external solutions on electrode – analytical characteristics of proposed sensor had been determinated. The selectivity coefficients (Кsel) of made sensor on relationships for inorganic (Pb2+; Ni2+; Cu2+; Cd2+; Zn2+; Ba2+; Fe3+; Bi3+; PO43- (1,0·10-3); Mg2+; Be2+; NO3-; SO42- (3,2·10-3); Cl- (5,0·10-3); K+, Mn2+, Br-, I- (1,0·10-2); Al3+ (2,2·10-2) Na+ (3,3·10-2)) and organic components (citric acid (1,0·10-3); thiourea (1,0·10-2); urea; oxalic acid; succinic acid; glucose (3,0·10-2)) ofbiological fluid were determinated by method of separated solutions. The determination of molybdenum (VI) contain in whole blood (sr=5,9 %) and urine (sr=5,9 %) samples was conducted by method of additions. The correctness of the obtained results was tested by alternative spectrophotometric technique. The reproducibility of proposed ionometric and alternative spectrophotometric techniques for Cochran's Q – test (Gexper < Gtabl) is the same. The proposed sensor can be used in clinical analyze of biological fluids, in particular in the whole bloodand urine samples of patients.